NILAI PENDIDIKAN DALAM KOMPILASI HUKUM ISLAM (KHI) SEBAGAI LANSKAP POLITIK HUKUM DI INDONESIA - Farida Ulvi Na’imah; Muslihun Muslihun (At-Tajdid: Jurnal Ilmu Tarbiyah, 2020)
In the context of fostering national law, Islamic law is now dealing with Western law and customary law. This research is a library research (Library Research), which is research that is directed and focused on the study and discussion of library materials that are related to the issues being studied, especially regarding the KHI discourse in the political and legal landscape in Indonesia. This research is descriptive-analysis in nature, that is, this research seeks to describe or explain how the KHI discourses in the political and legal landscape in Indonesia. The fiqh movement in Indonesia is a continuation of the orientation of Sufism which has been so strong and has emerged earlier. This is a logical consequence of the historical process that for the merits of the Sufilah Islam spread throughout the archipelago. The struggle to legalize Islamic law began to show its results, when finally Islamic law received constitutional juridical recognition. Various laws and regulations, most of the material taken from fiqh books which are considered representative, have been passed by the Indonesian government. Social fiqh presents itself as social ethics which is manifested in an institution called the state, an institution that kills the creativity of civil society and also the old pattern of thinking which is considered conservative.